2008
DOI: 10.1097/00042728-200810000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation 1,550-nm Fractional Photothermolysis for the Treatment of Acne Scars

Abstract: BACKGROUND AND OBJECTIVES Acne scars affect the entire population, causing significant distress and concern. Previous treatments for acne scars have yielded varying degrees of success and associated side effects. Fractional photothermolysis has been shown to improve scars, including surgical scars, hypopigmented scars, and atrophic acne scars. The newest system has the option of increased fluences for greater depth of penetration and variable treatment coverage. Our aim was to determine the efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 11 publications
2
40
0
1
Order By: Relevance
“…In line with literature data (4,5,(9)(10)(11)(12)(13), the present authors found that NFP is an effective and safe method, being accepted by all the patients with a high grade of satisfaction regarding results, intraoperative discomfort, and recovery time, without severe side effects. Herpes simplex infection is reported as a complication occurring in about 2% of patients treated with NFP (9).…”
Section: Discussionsupporting
confidence: 87%
“…In line with literature data (4,5,(9)(10)(11)(12)(13), the present authors found that NFP is an effective and safe method, being accepted by all the patients with a high grade of satisfaction regarding results, intraoperative discomfort, and recovery time, without severe side effects. Herpes simplex infection is reported as a complication occurring in about 2% of patients treated with NFP (9).…”
Section: Discussionsupporting
confidence: 87%
“…A single session of Fraxel ® SR1500™ treatment consisted of eight passes with a pulse energy of 40 mJ/cm 2 at level 6 (17% coverage/cm 2 /pass) 12,13 . The treated area usually became erythematous and swollen within several minutes.…”
Section: Methodsmentioning
confidence: 99%
“…At one month after final treatment, 18/29 showed 51–75% improvement and 5/29 patients showed > 75% improvement. Post treatment erythema resolved in 2–5 days .…”
Section: Non‐ablative Fractional Lasersmentioning
confidence: 99%